The Effect of Digital-Based Interactive Modules to Improve Student’s Critical Thinking Skills and Learning Motivation on Biology Learning - Jayanti Syahfitri; Desilia Safitri (Postgraduate, University of Mataram, 2024)
Biology learning is learning that requires teaching materials that can facilitate the delivery of abstract and complex material. This research aims to determine the effect of digital-based interactive modules on students' critical thinking skills and learning motivation at SMA Negeri 9 Bengkulu City. This research is a type of Quasi-Experimental research. The sample used in collecting research data was 65 students taken from class X MIPA 2 as the experimental class and X MIPA 3 as the control class. The instruments used were critical thinking skills test sheets and student learning motivation questionnaires. The results showed that students' critical thinking skills and learning motivation were better compared to the control class. This is shown by the significance value for these two variables, namely 0.00 0.05. The results of this research confirm that the use of teaching materials in the form of interactive digital modules in biology learning is effective in facilitating students to develop their thinking skills. The use of teaching materials that utilize technology will foster students' learning motivation because they are considered relevant to students' learning needs in the current technological era.